Kultivasi Mikroalga Menggunakan Media AF6 Berdasarkan Perbedaan Intensitas Cahaya - Nova Diyana Nurhanifah; Padil Padil; Sri Rezeki Muria (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Microalgae cultivation use AF6 media based on light intensity difference has done in this research. Light intensity has an important function in the process of photosynthesis. Optimization of light intensity is expected to increase growth microalgae. In the microalgaecultivation of laboratory scale used light lamp for substitute sunlight. This research purpose for determine the effect of light intensity differences on spesific growth rate on various microalgae cultivated in AF6 media. In this research observations of cell density microalgaechlorella sp. (6) and chlamydomonas sp. (4, 5, 19, chl) at media AF6 on the variation intensity 500 lux, 1.000 lux and 1.500 lux are did with testing the optical density of each microalgae with wavelength of 680 nm using UV-VIS spectrophotometer. The research resultexplain specific growth rate and shortest doubling time occurred in the light intensity 1.500 lux. Microalgae which has spesific growth rate and shortest doubling time are microalgae Chlorella sp.with value 0,78/day, and 0,88 day respectively.Keywords: light intensity, density, growth, microalgae